(untitled) (Journal of Comparative & International Higher Education, 2024)
Calling on the Foucauldian notion of entrepreneurial Selfhood, this thesis intends to uncover lived accounts of neoliberalism in Japanese higher education. Indeed, as a member of the Top Global University Project (TGUP), the host institution enacts openly neoliberal reform as one of the 37 ‘élite’ universities driving Japan’s academic reputation and human capital output. The global pivot toward neoliberal marketization has been subjected to fierce scholarly critique; however, despite these efforts, empirical phenomenological accounts of the Japanese entrepreneurial Self present a notable gap in the available literature that this thesis, in part, seeks to address. Drawing on interpretive phenomenological analysis, I hope to understand how the inculcation of specific neoliberal values, soft skills, and capitals (self-reliance, individuality, discipline, foreign language proficiency, cosmopolitanism) connect personhood and citizenship locally, specifically for nine learners (f=6, m=3) at a TGUP institution. Initial findings indicate that, in a nested terrain of shadow education, New Public Management, and hyper-competitive credentialism, graduation from brand-name colleges represents the final step for ‘responsible’ graduates to emerge as globally-orientated human capital. To achieve this journey, participants reported instances of entrepreneurial Selfhood from as young as elementary school, where the doxic pressures of Japan’s enterprise ontology compel youths to credentialise through prestige-graded private education, and the for-profit ‘shadowed’ learning providers facilitating admittance to these institutions.